2021
DOI: 10.3389/fmed.2021.712040
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Selection on the Appropriate FIT Cut-Off Point in CRC Screening Programs in the COVID Pandemic

Abstract: Background: The COVID pandemic has forced the closure of many colorectal cancer (CRC) screening programs. Resuming these programs is a priority, but fewer colonoscopies may be available. We developed an evidence-based tool for decision-making in CRC screening programs, based on a fecal hemoglobin immunological test (FIT), to optimize the strategy for screening a population for CRC.Methods: We retrospectively analyzed data collected at a regional CRC screening program between February/2014 and November/2018. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“… 80 Efforts to mitigate this survival decline are needed, mainly focusing on catching-up CRC screening programs and resuming at least the previous colonoscopy workload in the endoscopic units to meet the demands of screening and diagnostic colonoscopies backlog. Using surrogate biomarkers such as FIT, as well as stratification by other risk factors, 32 , 40 may be useful strategies to prioritize patients with higher risk while resuming the normal endoscopic activity, to minimize this forthcoming increase in CRC mortality by detecting the cases with a higher risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 80 Efforts to mitigate this survival decline are needed, mainly focusing on catching-up CRC screening programs and resuming at least the previous colonoscopy workload in the endoscopic units to meet the demands of screening and diagnostic colonoscopies backlog. Using surrogate biomarkers such as FIT, as well as stratification by other risk factors, 32 , 40 may be useful strategies to prioritize patients with higher risk while resuming the normal endoscopic activity, to minimize this forthcoming increase in CRC mortality by detecting the cases with a higher risk.…”
Section: Discussionmentioning
confidence: 99%
“… 31 However, increasing the colonoscopy capacity is not possible for every health system, so it has been suggested that increasing FIT cutoff or using specific risk factors (male sex and advanced age) could be an effective strategy to prioritize access to colonoscopies and reduced the number of CRC or advanced adenomas underdiagnosed in a CRC screening program, compared with randomly reducing the number of population screened. 32 Colon capsule endoscopy has also been advocated as an alternative for CRC screening after a positive FIT, as it can be performed as an out-of-clinic procedure, avoiding patients to attend medical facilities, and it has demonstrated a high diagnostic accuracy (area under receiver operating curve 0.963 for polyps at least 6 mm); hence, it may be used to filter patients in need of a colonoscopy. 33 In fact, current CRC screening guidelines recommend this technique as a valid alternative for individuals unable or unwilling to undergo colonoscopy.…”
Section: Impact Of Covid-19 Pandemic In Crc Screeningmentioning
confidence: 99%
“…-f-Hb <120 μg/g: repeat FIT in 3 years; [36,37], -f-Hb 120-180 μg/g: repeat FIT in 6 months. Colonoscopy only if repeated FIT result ≥180 μg/g; [38] and -f-Hb ≥180 μg/g: colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…In the discussion of a pandemic‐resilient CRCS, our results may suggest new fundamental elements. Currently examined solutions are mainly regarding: (1) enhancing the participation rate (mailed FIT program 37 and shift toward a more FIT‐focused CRCS 38 ); and (2) improving efficiency for an increased yield (readjustment of the cutoff value of FIT and risk‐stratified colonoscopy based on FIT result 39 ). However, solutions for avoiding a shutdown of cancer screening are not explicitly discussed.…”
Section: Discussionmentioning
confidence: 99%